Rekonstruksi Khilafah Dalam Al-Qur’an - Mabroer Inwan (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2018)
This Paper examinies the views of Quraish Shihab against the arguments used by HTI and refutes the legitimacy concept khilâfah in three aspects. Firstly, the obligation to enforce Islamic law in QS. al-Mâ’idah [5]: 48. Secondly, the obligation of amar ma’ruf nahi munkar and the last is the obligation to obey with Allah, Rasul and ulil amr. Of these three foundations, Quraish Shihab sees the obligation to enforce Islamic law in the QS. al-Mâ’idah [5]: 48 deemed necessary to apply the law of God, just not to emphasize God’s law absolutely while amar ma’ruf nahi munkar in the QS. Ali ‘Imrân [3]: 110 assessed the obligation of amar ma’ruf nahi munkar related obligation invites to the good that ma’ruf in line with the value of goodness in the culture of society as well as the obligation to present doing something that can demage in QS. an-Nisâ’ [4]: 59 Quraish Shihab emphasize the obligation of obedience to Allah, Rasul and ulil Amr a daty, just only that obligation to obedient with ulil amr are those who bring a good values a mong them of the rulers/government, other meaning is ulama and the letter representing the community in these various groups and professions. In so doing, the author reters to his work “Tafsir al Misbah; Pesan, Kesan dan Keserasian Al-Qur’an” and several other works, with literary interpretation, the author review and analyze with the work of interpretive and analytical and comparative analytic approach with the interpretation of HTI.